Recent Developments on the Synthesis of Oxygen- and Sulfur-containing Heterocycles and their Derivatives under Visible Light Induced Reactions - Ghosh, Tubai; Santra, Sougata; Zyryanov, Grigory V.; Ranu, Brindaban C. (Current Topics in Medicinal Chemistry, 2025)
Visible-light-mediated reactions have recently emerged as a powerful strategy for the synthesis of diverse organic molecules under mild reaction conditions. Usually, the reactions are performed at room temperature and thus sensitive functional groups remain unaffected. Thus, this protocol has received intense interest from academia as well as industries. The heterocycles, in general, are of much interest because of their biological activities and application in therapeutics. The Oxygen- and Sulfur-containing heterocyclic compounds have recently attracted attention as these compounds showed promising activities as anti-cancer drugs, antibiotics, antifungal and anti-inflammatory agents among other applications. The synthesis of this class of compounds by efficient and greener routes has become an important target. This review highlights the various procedures for the synthesis of these compounds and their derivatives under visible light-induced reactions. The green aspects and mechanism of each procedure have been discussed.
Keywords: Visible light